Increased Revenues in Beef Cattle Business in Hamlet I Kelambir V Village in Hamparan Perak Sub-District Deli Serdang Regency - Marisa, Julia; Sitepu, Sukma Aditya (Journal of Saintech Transfer, 2018)
This community service aims to introduce revenue analytics in beef cattle business to breeders in order to know the amount of their income in every scale of livestock ownership level in Hamlet I, Kelambir Village, Hamparan Perak Sub-District, Deli Serdang Regency. This activity was expected to improve the ability and increase the knowledge of beef cattle breeders to do self-analysis on how to separate accepted and cost components to be incurred in one period of care. Thus, it would be easier for the breeders to calculate the total income in one period of beef cattle breeding which will improve their welfare. The impact brought from this program was that a number of breeders have understood about revenue analytics and started to calculate the total income they have had. Therefore, they can learn to make the production cost of their business efficient which leads to an increased revenues.